A dominant, pan-DR binding epitope of Der p 1 in house dust mite allergy induces tolerance in HLA-DR4 transgenic mice - Streeter, Heather B.; Lucas, Lora G.; West, Robert M.; Krishna, Mamidipudi T.; Wraith, David C. (Frontiers in Immunology, 2025)
BackgroundPeptides were designed to induce immune tolerance to the major antigen associated with house dust mite (HDM) allergy, Der p 1. HDM is commonly associated with allergic responses in allergic rhinitis and asthma, with Der p 1 specific T-cells implicated in ongoing disease. Tolerogenic peptide immunotherapy can induce tolerance in pathogenic T-cells, bypass mast cell activation and hence reduce the risk of anaphylaxis. A pan-DR binding epitope of Der p 1, covering the broad population, was tested for efficacy in HLA-DR transgenic mice.MethodsPotential pan-HLA-DR binding tolerogenic T-cell epitopes from Der p 1 were predicted in silico and manufactured (synthetic peptides A-E). Participants included HDM sensitised (allergic rhinitis/asthma, n=25), non-HDM sensitised (atopic controls sensitised to ≥1 other aero-allergens, n=10) and non-atopic healthy controls, n=10). Peripheral blood mononuclear cells (PBMC) were collected and screened for immune responses to Der p 1 or test peptides A-E. Mapping of minimal T-cell epitopes, apitope (antigen-processing independent epitope) validation and tolerance induction were tested in HLA-DR transgenic mice.ResultsHDM-sensitised subjects have an elevated response to pan-DR binding peptide D 30mer. Peptide analogue D121B, containing the minimal epitope and optimised for solubility, was verified as a tolerogenic apitope and induced tolerance against Der p 1 antigens in HLA-DR4 transgenic mice in vivo.ConclusionA tolerogenic peptide, apitope D121B, reduces T-cell immune responses to Der p 1 and is a promising candidate for further development as an immunotherapy for HDM-associated allergic rhinitis and asthma.